2010
DOI: 10.1007/s10549-010-0750-1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of vacuum-assisted breast biopsy for breast carcinoma: a meta-analysis and systematic review

Abstract: As mammography screening has its limitation in diagnosis in breast carcinoma, minimally invasive procedures offer a better option. We conducted a systematic review to establish the overall value of Vacuum-assisted breast biopsy (VAB) for the diagnosis of breast cancer. After a review and quality assessment of 21 studies, sensitivity, specificity and other measures of accuracy of VAB for evaluating breast lesions were pooled using random-effects models. Summary receiver operating characteristic curves were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 71 publications
2
41
0
6
Order By: Relevance
“…11G and 8G) are now considered the gold standard and are in widespread use in the UK. VACB provides a larger tissue sample and improves both the accuracy of classification of grade of DCIS and greater assurance of the absence of invasion [10,11]. SIZE DCIS size eligibility criteria were a contentious issue during the protocol design.…”
Section: Gradementioning
confidence: 99%
See 1 more Smart Citation
“…11G and 8G) are now considered the gold standard and are in widespread use in the UK. VACB provides a larger tissue sample and improves both the accuracy of classification of grade of DCIS and greater assurance of the absence of invasion [10,11]. SIZE DCIS size eligibility criteria were a contentious issue during the protocol design.…”
Section: Gradementioning
confidence: 99%
“…The main challenges so far have been slow site set-up (eleven sites are now open at six months; the mean time for setting up sites in the UK in 2014 is 9.7 months [30]) and the reluctance of NHS Trusts to fund first line VACBs, despite much published evidence that they are the gold-standard for evaluation of microcalcifications and have a better concordance with excision histology than small volume cores [10,11].…”
Section: Trial Progressmentioning
confidence: 99%
“…ER+ depend on estrogen for their growth, so they can be treated with drugs to block estrogen effects (e.g. tamoxifen), and generally have a better prognosis (Yu YH et al, 2010) HER2+ cancer cells respond to drugs such as the monoclonal antibody trastuzumab (in combination with conventional chemotherapy), and this has improved the prognosis significantly (American cancer society, 2012). Cells those do not have any of these three receptor types are called triple-negative, although they frequently do express receptors for other hormones, such as androgen receptor and prolactin receptor.…”
mentioning
confidence: 99%
“…Biopsy is a common method in diagnosis of BC [75-77], which is consistent with our findings (Table 1). In addition, another study found that vacuum-assisted breast biopsy had high levels of diagnostic accuracy and sensitivity when evaluating mammographically detected breast by performing a meta-analysis [78]. A screening MG was used to examine the breasts of an asymptomatic woman, while a diagnostic MG was performed in a patient presenting with signs or symptoms of breast disease: a possible abnormality detected on screening MG or other imaging, or prior MG findings requiring imaging follow up [79].…”
Section: Discussionmentioning
confidence: 99%